1975
DOI: 10.1139/x75-064
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Control of Cold Acclimation in Douglas Fir During Germination, Active Growth, and Rest

Abstract: Controlled-environment experiments were conducted on Douglas-fir (Pseudotsugamenziesii (Mirb.) Franco) seedlings during their 1st year. Hardiness of foliage was assessed by visually estimating injury after freezing tests.Germinants (1 week) were unable to attain any freezing tolerance under 8-h days at 2 °C even after 9 weeks but were killed whenever ice formed. Their ability to supercool increased by 5 °C during this treatment. However, seedlings older than 3 weeks (1 to 2 cm of epicotyl) could develop true h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1977
1977
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Neither of these studies, however, indicates the developmental stage of seedlings at the beginning of the treatment or when they were freeze tested. Finally, Timmis and Worrall (1975) also reported that 7-week-old seedlings (2-cm epicotyl) of Pseudotsuga menziesii reacted to low temperature treatments by increasing their frost tolerance and that 1-week-old seedlings submitted to low-temperature treatments also reacted in the same way, but not until their epicotyl had started elongating.…”
Section: Hardening Capacity Of Different Developmental Stagesmentioning
confidence: 88%
See 1 more Smart Citation
“…Neither of these studies, however, indicates the developmental stage of seedlings at the beginning of the treatment or when they were freeze tested. Finally, Timmis and Worrall (1975) also reported that 7-week-old seedlings (2-cm epicotyl) of Pseudotsuga menziesii reacted to low temperature treatments by increasing their frost tolerance and that 1-week-old seedlings submitted to low-temperature treatments also reacted in the same way, but not until their epicotyl had started elongating.…”
Section: Hardening Capacity Of Different Developmental Stagesmentioning
confidence: 88%
“…According to Timmis and Worrall (1975), 3-(1 cm long epicotyl) and 7-week-old (2 cm long epicotyl) seedlings of Pseudotsuga menziesii (Mirb.) Franco reacted to a lowtemperature -short-photoperiod treatment by increasing their frost tolerance, and the degree of response increased with age.…”
Section: Introductionmentioning
confidence: 99%
“…It also may have been a response to desiccation [26], as desiccated tissues are more cold hardy than fully hydrated ones [28]. While seedlings exposed to colder temperatures during the early stages of hardening can cold harden more quickly, it has been shown elsewhere that premature exposure to cold temperatures can prevent the attainment of maximal cold hardiness [12,36].…”
Section: Cold Hardinessmentioning
confidence: 99%
“…), although this practice has not been studied explicitly (van den Driessche 1970;Aronsson 1975;Jonsson et al 1981;Johnsen 1989a). Occurrence of frost nights during the dormancy induction period has been shown to induce deeper hardiness in both angiosperms (Junttila and Kaurin 1990) and conifers (Timmis and Worral 1975;Greer and Warrington 1982;Hawkins 1993;Silim and Lavender 1994). The impact of frost nights as they might occur in nature during early autumn has, to our knowledge, not been studied experimentally using controlled freezing chambers in Norway spruce.…”
Section: Introductionmentioning
confidence: 98%